2021
DOI: 10.1002/tox.23361
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG14 contributes to proinflammatory cytokine production in rheumatoid arthritis via the regulation of the miR‐17‐5p/MINK1‐JNK pathway

Abstract: Rheumatoid arthritis (RA) is a widespread autoimmune disorder of the joints. Long noncoding RNAs (lncRNAs) have been reported to participate in the pathogenesis of RA by serving as competitive endogenous RNAs. LncRNA small nucleolar RNA host gene 14 (SNHG14) is involved in the development of various diseases. Here, we found that high expression of SNHG14 in RA was closely related to the disease activity. Functional assays indicated that SNHG14 knockdown obviously hampered phorbol myristate acetate-activated TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Moreover, similar to the key roles of miRNAs in human pathology ( 34 40 ), deregulated lncRNA expression has been documented in many kinds of diseases, such as degenerative diseases, tumors, cardiovascular disease, and autoimmune/inflammatory diseases ( 41 48 ). Recently, an increasing amount of evidence suggested that lncRNAs also actively take part in development of orthopedic diseases, including scoliosis, intervertebral disc herniation, arthritis and AS ( 49 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, similar to the key roles of miRNAs in human pathology ( 34 40 ), deregulated lncRNA expression has been documented in many kinds of diseases, such as degenerative diseases, tumors, cardiovascular disease, and autoimmune/inflammatory diseases ( 41 48 ). Recently, an increasing amount of evidence suggested that lncRNAs also actively take part in development of orthopedic diseases, including scoliosis, intervertebral disc herniation, arthritis and AS ( 49 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we suggest MINK1 as a novel candidate gene for autism, congenital cataract, epilepsy and osteoporosis. Although we report the first patient with disruption of MINK1 , the gene has already been implicated in a variety of disorders based on cohort studies in humans, in silico models and work on model organisms, including congenital heart disease in humans [ 20 ] and skeletal and neuronal phenotypes in mice [ 21 , 22 ], as well as cancer [ 23 , 24 ], platelet formation [ 25 ], Alzheimer disease [ 26 , 27 ] and arthritis [ 28 ]. As such, it appears that MINK1 is part of a diverse set of biological processes, which is expected as MINK1 is highly expressed in a variety of tissues ( Figure 2 B) and interacts with a diversity of proteins ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. showed that lncSNHG14 can promote misshapen-like kinase 1 (MINK1) expression through a ceRNA mechanism, ultimately increasing pro-inflammatory cytokine expression in rheumatoid arthritis ( 104 ).In LPS induced acute lung injury, lncSNHG14 was reported to be induced and mediate Wnt1 inducible signaling pathway protein 1 (WISP1) expression by sponging miR-34c-3p, thus promoting proinflammatory proteins IL-18, IL-1β, TNF-α and IL-6 ( 105 ).…”
Section: Lncsnhg-mediated Anti-tumor Immune Responsesmentioning
confidence: 99%